2013
DOI: 10.1093/gji/ggt352
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence conditions of roll waves for three grain–fluid models and comparison with results from experiments and field observation

Abstract: For the flow and deposition behaviour of debris flows, phenomena like particle sorting, levee formation and the development of roll waves are expected to be important processes. However, these processes are not well understood and hardly implemented in modelling approaches. In this study, we focus on the development of roll waves and derive advanced criteria separating stable and instable flow regimes for three debris flow models. These criteria are expressed using critical Froude numbers. Each of these simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We infer length and mean velocity of debris flow surges in alpine regions from hydrographs reported by Arai et al . [] with 100–500 m and 5–10 m/s, respectively, and calculate an upper bound of T fc,DF ~ 10 1 s, which is 1 order of magnitude longer than in our experiments.…”
Section: Discussionmentioning
confidence: 70%
“…We infer length and mean velocity of debris flow surges in alpine regions from hydrographs reported by Arai et al . [] with 100–500 m and 5–10 m/s, respectively, and calculate an upper bound of T fc,DF ~ 10 1 s, which is 1 order of magnitude longer than in our experiments.…”
Section: Discussionmentioning
confidence: 70%
“…Observations from debris-flow monitoring stations, like at Lattenbach (Arai et al 2013), Illgraben (Rickenmann et al 2001;Hürlimann et al 2003), the Moscardo torrent (Marchi et al 2002) or Chalk Cliffs (McCoy et al 2011), lack superelevation data. Mizuyama and Uehara (1981) as well as Ikeya and Uehara (1982) first analysed the application of the forced vortex equation for debris-flow velocity estimates, based on the results of small-scale laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Critical Froude number is widely used as the criteria separating the existence of the roll wave or not (Arai et al, 2013;Jeffreys, 1925;Smith et al, 2011;Thual, 2013). Several researchers, among them Ishihara et al (1954), Benjamin (1957), Yih (1963Yih ( , 1977 and Ferreira et al (2015) indicated that for laminar flow down an inclined plane, the roll waves tended to form when the Froude number was greater than 0.58.…”
Section: Introductionmentioning
confidence: 99%